Clinical and echocardiographic factors associated with complications in patients with acute myocardial infarction - Yoandro Rosabal Garcia; Níger Guzman Pérez; Eddy Alberto Rosales Guibert (Revista Habanera de Ciencias Médicas)
Introduction: Acute myocardial infarction is the leading cause of death and disability worldwide, accounting for almost one-third of all deaths and nearly half of non-communicable diseases.